Language interpretation and translation in emergency care: A scoping review protocol. - Henry Li; Samina Ali; Lisa Hartling; Liz Dennett; Elena Lopatina; Kayathiri Ganeshamoorthy; Jaspreet Khangura (PLoS ONE)
Introduction Patients with preferred languages other than English face barriers to communication and access to appropriate care in English-speaking emergency care systems, leading to poorer communication and quality of care, as well as increased rates of investigations and healthcare utilization. While professional interpretation can help bridge this gap, uptake is exceedingly poor, suggesting the need for enhanced implementation and more accessible modalities. Our study will map the existing literature on interpretation/translation in emergency care, with a focus on the breadth of modalities, barriers/facilitators to implementation, and effectiveness/implementation outcomes. Methods We will conduct a scoping review based on the Joanna Briggs Institute methodology. We will search MEDLINE, Embase, PsycINFO, CINAHL, Scopus, iPortal, Native Health Database and Cochrane Library CENTRAL for articles from inception to May 2024 without any language or country restrictions. Primary research articles involving interpretation/translation between English and a non-English language during emergency healthcare encounters will be included. Screening and data extraction will be completed by two independent team members. Results will be descriptively summarized and barriers/facilitators to implementation will be mapped according to the Consolidated Framework for Implementation Research. Stakeholder engagement & knowledge translation Results will be disseminated at academic conferences and published in a peer-reviewed journal. We will share our key findings via a graphical abstract and social media campaign. Our team includes our provincial health authority interpretation services lead who brings lived experience and will inform and validate our results and help identify future areas of needed research. They will also help us identify key messages and appropriate methods for dissemination to maximize knowledge translation to patients/families, local policy/clinical practice, as well as funding agencies.